COVID-19: WAYS TO IMPROVE TREATMENT OUTCOMES. TRANSFORMING PERCEPTIONS ABOUT INTENSIVE CARE OF CORONAVIRUS INFECTION - Dmytro D. Diachuk; Oleg L. Ziukov; Volodymyr I. Cherniy; Oleksandr V. Naumenko; Anatolii I. Denysenko (Клінічна та профілактична медицина, 2025)
Introduction. Given the lack of effective specific antiviral therapy for COVID-19, the main focus is currently on symptomatic and respiratory support. Almost all hospitalized patients are recommended to undergo oxygen therapy, while the WHO recommended extracorporeal membrane oxygenation for patients with refractory hypoxemia.